Can the Sup-ER Protocol Decrease the Prevalence and Severity of Elbow Flexion Deformity in Brachial Plexus Birth Injuries?. (January 2023) - Yefet, Leeor; Bellows, Doria; Bucevska, Marija; Courtemanche, Rebecca; Durlacher, Kim; Hynes, Sally; Verchere, Cynthia
Background: Brachial plexus birth injuries (BPBIs) can often result in functional and cosmetic deficits including, according to a recent scoping review, elbow flexion contractures in up to 48%. A treatment algorithm that includes a custom long-arm orthosis to optimize early glenohumeral joint positioning (Sup-ER protocol) has been shown to improve shoulder range of motion. Although the protocol was not intentionally designed to affect the elbow, this study investigates the prevalence and severity of elbow flexion contractures in children treated with that protocol. Methods: This prospective cross-sectional cohort study examined 16 children aged 4 and older with BPBI severe enough to be treated with the Sup-ER protocol. Passive and active elbow flexion and extension range of motion (ROM) were assessed in both arms. Elbow flexion contractures were defined as > 5 o from neutral. Results: Within the cohort of 16 patients (mean age: 7.0 years, range: 4.5-11.6 years), the mean maximal passive elbow extension was -6.2° in the affected arm and + 5.1° (hyperextension) in the unaffected arm. Zero patients had a severe elbow flexion contracture (>30 o ) and only 6/16 met the lowest threshold definition of elbow flexion contracture (>5 o ), with a mean onset at 22 months of age. Conclusions: This study suggests an unintended decreased prevalence and severity of elbow flexion contractures in children with more severe BPBI treated with the Sup-ER protocol, relative to published values.